دور النخبة التونسية في مواجهة سياسة التجنيس في تونس 1885-1933م - غربي، روضة; شاوي، يمينة (University Of Eloued جامعة الوادي, 2024)
ان المتصفح لتاريخ تونس خلال الفترة الاستعمارية تستوقفه ظاهرة مثلت واحدةمن القضايا الاكثر انتهاك لشعور الشعب التونسي واستنهاظا لوعيه وذلك لخطورتها وتاثيرها على كيانه التاريخي والحضاري ونعني بذلك مشكلة التجنيس المشروع الذي وفرت ظروفه وساعدت على انجازه تنوع الجاليات والطوائف المتعايشة بتونس على امتداد الحقبة الاستعماريةولذلك كانت مشكلة تجنيس التونسيين واحدةمن قضايا الاحتكاك بين سلطة الحمايةوالنخبة التونسية لما لهذه القضية من مساس بهوية الشعب التونسي واصالته واعتبرتها النخبة التونسية هجمة من هجمات المسيحية ضد الاسلام لان القضية لها مساس بالعقيدة وهذا ما جعل النخبة التونسيةبمختلف تياراتها الفكريةوالعلميةوالسياسية تعلن رفضها لهذا المشروع وفي كثير من المواقف خاصة بعد صمت علماء الدين الرسميين الذين لم يوضحوا موقف الدين من التجنيس والمتجنس مستعملة عده وسائل لذلك كما عملت على توعية الشعب بخطورتها وذلك لترسيخ دعائم الدين والهويةالتونسية. The browser of the history of Tunisia during the colonial period is stopped by a phenomenon that represented one of the issues that most violated the feelings of the Tunisian people and aroused their awareness due to its danger and its impact on their historical and civilizational entity. We mean by that the problem of legitimate naturalization, the conditions for which were provided and helped to be accomplished by the diversity of communities and sects coexisting in Tunisia throughout the colonial era. Therefore, the problem of naturalizing Tunisians was one of the issues of friction between the protectorate authority and the Tunisian elite because this issue affects the identity and authenticity of the Tunisian people. The Tunisian elite considered it an attack by Christianity against Islam because the issue affects the faith. This is what made the Tunisian elite, with its various intellectual, scientific and political currents, announce its rejection of this project in many situations, especially after the silence of official religious scholars who did not clarify the position of religion on naturalization and the naturalized person, using several means for that. It also worked to educate the people about its danger in order to consolidate the pillars of religion and Tunisian identity.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: سياسة التجنيس في تونس; Naturalization policy in Tunisia